Does problem‐based learning facilitate enactment of learner agency in undergraduate dental curricula? A Q study - Kamran Ali (8861576) (2022)
Introduction Addressing a literature gap on leaner agency in health profession education, this study explores students' perceptions on which aspects of a problem‐based learning (PBL) environment cradle their leaner agency enactment. Methods Thirty‐eight students from a newly established undergraduate dental medicine programme in Qatar participated in the study. Q methodology was adopted to collect and analyse data both qualitatively and quantitatively. A 40‐statement Q‐set was established based on a proposed conceptual framework of learner agency in PBL, including three dimensions—intrapersonal, behavioural and environmental. Results Q methodological factor analysis identified four significantly different student viewpoints, which underscored participants' enactment of learner agency addressing the intrapersonal, behavioural and environmental dimensions of the conceptual framework. Despite differences in opinion regarding sources of learner agency, the four student viewpoints unanimously underscore the importance of PBL facilitators' expertise to nurture and develop agency amongst undergraduate students. Post‐sorting qualitative data further confirmed the quantitative analysis. Time constraints and workload were identified as the main challenges by the participants. Conclusions This study explored enactment of learner agency as perceived by undergraduate dental students in a PBL curriculum. The findings of this study provide new insights into participants' subjective understanding of learner agency in a PBL curriculum in dentistry. Structured support is needed for students having no prior PBL experiences to develop their learner agency at both intrapersonal and behavioural (self‐regulated learning) dimensions, and to ensure they interact with their learning environment proactively. Other Information Published in: European Journal of Dental Education License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/eje.12872